Belgrano, Echeverría, Gessell - Popescu, Oreste (1960)
The argentine economic development in Manuel Belgrano`s Thought: The author introduces us in his study by giving a short account of the variations political economy in the course of the last quarter of the century. It is important to note that the first part of this article explains the nature of economic development as well as the influence exercised by long run movements. Manuel Belgrano one of our first economists, has left us in his "Memories" the "first ideas for a theory of Argentine economic development" as he was intellectually one century ahead of his contemporaries. According to Manuel Belgrano "economic development is part of the socio-cultural development; economic development is an harmonic process; economic development is concordant with free market economy". Estevan Echeverria, fore runner of solidaristic economic theories: His christian universalism as well as his adhesion to the "theory of perfectibility" did not impede Echeverria to agree at the same time with the dogma of "human rights", mainstay of nationalistic philosophy. It is on the basis of the solidarity law that he establishes his social philosophy, which later was adopted by the majority of western economists and politicians. Among the natural human rights Echeverria considers the property right and sustains that it should be adapted to social necessities and interests. He sees in the economic development the principal element for the achievement of the supreme law of progress which in turns is conditioned by the time factor, avoiding class struggles. Completely independent from H. V. Thünen. Echeverria reaches the same conclusions and establishes the tax system upon the principle of location advantages. Between the two extreme concepts – individual and humanity – he intercalates the idea of nationality becoming thus the fore runner of the "national school of Argentine political economy". Although he is a defender of economic freedom, he nevertheless admits state interventions, providing they are aimed to increase social welfare, the production of national wealth and the moral intellectual and physical improvement of the numerous poor classes. Silvio Gesell: The author describes Gesell's life since he settled in Argentina where he devoted himself to his business, being specially attracted by the analysis of economic and social problems. After a through examination of Gesell's writing, the author explains his economic theory which is intimately connected with his social doctrine, and describes the gesellian and post-gesellian movement. The thinks that the attitude of absolute reserve which economists maintained during almost thirty years with regard to Gesell and his teaching was not so much due to his caustic and offensive spirit, as to the fact that he had the presumption to solve the most difficult economic problem which ever faced noted scholars: the problem of interest. His perseverance as well as that of his disciples, particularly Theophil Cristen, forced the economists to break the silence, thus giving origin to a series of monographics in which critical analysis are made with ever increasing objectivity and depth.